THU0268 Decreased Expression of MIR-130A and MIR-708 in Type-1 Classical Dendritic Cells of Sjögren's Syndrome Patients Indicates Their Dysregulation. (15th July 2016) - Hillen, M.R.; Blokland, S.L.; Chouri, E.; Lopes, A.P.; Kruize, A.A.; Hack, C.E.; Rossato, M.; Radstake, T.R.; van Roon, J.A.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease characterized by lymphocytic infiltration of the salivary and lachrymal exocrine glands that leads to dryness of mouth and eyes. Type-1 classical dendritic cells (cDCs) are very potent antigen presenting cells known to induce strong T-cell proliferation and cytokine production. Despite the fact that especially cDC1s are candidate key players in the activation of local T and B-cells in pSS, they have rarely been studied in pSS. Objectives: Considering the critical role of micro-RNAs (miRNAs) in regulation of gene expression, we investigated miRNA expression in isolated cDC1s of pSS patients. Methods: Two independent cohorts (discovery and validation) were established including a total of 29 pSS patients. 17 healthy controls (HC) were included as control group. cD1c+CD19- cells were isolated from peripheral blood using MACS and we performed miRNA profiling of 758 miRNA targets using the OpenArray platform in the donors included in the discovery cohort. A selection of the miRNAs found to be differentially expressed in pSS versus HC was measured in the validation cohort. We performed pathway enrichment with the experimentally supported targets of the validated miRNAs. Results: A total of 24 miRNAs were downregulated in pSS patients versus HC in the discovery cohort (all at least p<0.05 and 2log expression difference). Of these, 16 targets were selected to be validated in validation cohort. Two miRNAs, miR-130a and miR-708, were significantly downregulated in pSS patients in both cohorts (p<0.05). Pathway enrichment showed that the experimentally supported targets of these miRNAs are mainly involved in vesicle trafficking and a number of growth-factor signalling pathways (p<0.05, FDR corrected), including epidermal growth factor (EGF) signalling and endocytosis. We are currently linking the miRNA expression data to RNAseq data and performing functional experiments with primary DCs to dissect the effects of miRNA dysregulation in these cells. Conclusions: We here for the first time show differentially expressed miRNAs in an isolated immune cell subset of pSS patients. In addition, this is the first evidence for dysregulation of primary peripheral blood type-1 cDCs in pSS. Considering threimportant role of miRNAs in cell function, this suggests that targeting aberrant miRNA expression may provide tools to modulate cDC activity. Disclosure of Interest: None declared